Challenges and facilitators to parent–child shared physical interventions during preschool and school age education: a systematic review and meta synthesis - Xiong, Lijuan (Frontiers in Public Health, 2025)
BackgroundDespite strong evidence supporting physical activity’s role in children’s physical, cognitive, and emotional development, many preschool and school-aged children fail to meet recommended activity levels. Parent–child shared physical activity interventions offer a promising approach, yet their implementation is influenced by multiple contextual factors. This study aimed to explore the challenges and facilitators of parent–child shared physical activity interventions in preschool and school-aged education settings.MethodsA comprehensive literature search was conducted across six databases—PubMed, Scopus, Web of Science, PsycINFO, Embase, and Google Scholar—using a combination of MeSH terms and keywords related to children, parents, shared physical activity, and implementation factors. Inclusion criteria focused on qualitative or mixed-method studies involving parents, educators, or stakeholders of children aged 3–11 years engaged in shared physical activity. Studies were screened and appraised using the CASP checklist. Qualitative data were analyzed using conventional content analysis, allowing for the identification of themes and subthemes.ResultsFour high-quality studies met the inclusion criteria. Two overarching categories emerged: challenges and facilitators. Key challenges included environmental and Structural Barriers, parental attitudes and low engagement, child-related challenges to participation and sociocultural and cognitive Influences on participation. Facilitators encompassed motivational strategies to encourage participation, program design that supports family engagement, strengthened parent–child relationships and institutional and environmental enablers.ConclusionParent–child shared physical activity interventions are most effective when they are culturally appropriate, developmentally suitable, and adaptable to daily routines. Overcoming structural and behavioral barriers through coordinated support from families, educators, and communities is essential for their long-term success.